Homologous recombination occurs in Entamoeba and is enhanced during growth stress and stage conversion. - Nishant Singh (Public Library of Science (PLoS), 2013)
Homologous recombination (HR) has not been demonstrated in the parasitic protists Entamoeba histolytica or Entamoeba invadens, as no convenient method is available to measure it. However, HR must exist to ensure genome integrity, and possible genetic exchange, especially during stage conversion from trophozoite to cyst. Here we show the up regulation of mitotic and meiotic HR genes in Entamoeba during serum starvation, and encystation. To directly demonstrate HR we use a simple PCR-based method involving inverted repeats, which gives a reliable read out, as the recombination junctions can be determined by sequencing the amplicons. Using this read out, we demonstrate enhanced HR under growth stress in E. histolytica, and during encystation in E. invadens. We also demonstrate recombination between chromosomal inverted repeats. This is the first experimental demonstration of HR in Entamoeba and will help future investigations into this process, and to explore the possibility of meiosis in Entamoeba.